Analisis Peranan Pamali Masyarakat Adat Sunda Terhadap Perkembangan Moral Anak Usia Dini - Ina Farida Arif; Aan Listiana (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2023)
The Sundanese indigenous people are famous for their cultural wisdom, namely pamali. Pamali as a typical Sundanese cultural product has a conditional meaning for children's development that needs to be continuously explored. This study aims to analyze the existence and moral development contained in the pamali of the Sundanese indigenous people in early childhood. This type of research is a systematic review of 20 journals with related criteria using qualitative methods. through the syntax, in literature, there are five traditional villages and two Sundanese villages that still apply pamali as part of the order of life and rules that have been passed down from generation to generation. Each of these pamali contains moral values ​​such as discipline, humility, care for the environment, and politeness which are reflected in the sentence of pamali. In line with Kohlberg's moral development, early childhood is included in the level 1 category, namely pre-conventional morality. The implications for children can be seen from how they can know when the taboos are through an understanding of taboos so it is hoped that this will foster an attitude of obedience to the rules that surround them to strengthen their knowledge of the cultural values ​​of the area.